2017
DOI: 10.5194/acp-17-13001-2017
|View full text |Cite
|
Sign up to set email alerts
|

Emission characteristics of refractory black carbon aerosols from fresh biomass burning: a perspective from laboratory experiments

Abstract: Abstract. The emission characteristics of refractory black carbon (rBC) from biomass burning are essential information for numerical simulations of regional pollution and climate effects. We conducted combustion experiments in the laboratory to investigate the emission ratio and mixing state of rBC from the burning of wheat straw and rapeseed plants, which are the main crops cultivated in the Yangtze River Delta region of China. A single particle soot photometer (SP2) was used to measure rBC-containing particl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 61 publications
14
59
1
Order By: Relevance
“…These results agree with Pan et al (2017) who observed significantly lower rBC emission ratios during the ignition of wet wheat straw (more smoldering; ER = 7.1 ng·m −3 ·ppbv −1 ) than the ignition of dry wheat straw (more flaming; ER = 25.3 ng·m −3 ·ppbv −1 ). Since MCE was >0.9 for all burns indicating either flaming-dominated or a mixed flaming-smoldering phase, we use ER (rBC/CO) to determine the combustion regime in our laboratory data.…”
Section: Optical Properties Of Laboratory Bb Emissionssupporting
confidence: 92%
“…These results agree with Pan et al (2017) who observed significantly lower rBC emission ratios during the ignition of wet wheat straw (more smoldering; ER = 7.1 ng·m −3 ·ppbv −1 ) than the ignition of dry wheat straw (more flaming; ER = 25.3 ng·m −3 ·ppbv −1 ). Since MCE was >0.9 for all burns indicating either flaming-dominated or a mixed flaming-smoldering phase, we use ER (rBC/CO) to determine the combustion regime in our laboratory data.…”
Section: Optical Properties Of Laboratory Bb Emissionssupporting
confidence: 92%
“…In terms of coated BC particles selected by DMA, the frequency distribution of CT exhibits three peaks, which characterize the coating materials of thinly coated BC (the first peak with the least CT ), thickly coated BC with single charge (the second peak with the medium CT ), and thickly coated BC with double/triple charges (the third peak with the most CT ), respectively. In this study, the thinly coated BC and thickly coated BC particles are distinguished based on the two‐mode distribution of lagtime (Figure S1), which is an indicator of BC mixing state (Moteki & Kondo, ; Pan et al, ). Larger lagtime can characterize more coating material on BC surface.…”
Section: Resultsmentioning
confidence: 99%
“…The validity of the LEO method for ambient BCcontaining particles observed in China has been evaluated by Y. . More details on the SP2 technique have been reported elsewhere (Gysel et al, 2011;Pan et al, 2017;Sedlacek et al, 2012;.…”
Section: Instrumentationmentioning
confidence: 99%
“…D c was calculated from m rBC and the density of the rBC core (ρ c ; here, a prescribed value of 1.8 g cm −3 ) (Cappa et al, 2012;Pan et al, 2017;Laborde et al, 2013). D p was determined via the Mie calculation and was related to D c , the C s of the BC-containing particle, and the refractive indices of NR-CM (RI NR−CM , 1.5-0i; Zhang et al, 2018) and rBC core (RI c , 2.26-1.26i; Taylor et al, 2015).…”
Section: Aging Degree Of Bc-containing Particlesmentioning
confidence: 99%
See 1 more Smart Citation